1979
DOI: 10.1145/322139.322150
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Algorithms for Some Postman Problems

Abstract: Approxtmatton algorithms for several NP-complete edge-covermg routing problems are presented and analyzed m terms of the worst-case ratio of the cost of the obtained solutmn to the cost of the optimum solutton A worst-case bound of 2 is proved for the mixed postman algortthm of Edmonds and Johnson, and a related algorithm for the mixed postman problem is shown also to have a worst-case bound of 2 A mixed strategy approach ts used to obtain a bound of ~ for the mixed postman problem A second mixed strategy algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 13 publications
2
82
0
Order By: Relevance
“…In contrast to Rural Postman, whose unweighted variant is NP-hard [12], we can show that EE and MEE are polynomial-time solvable. Altogether, our work complements and extends known results for WMEE with restricted weight function [11] and Rural Postman, for which mainly approximation, heuristic, and some polynomial-time algorithms for special cases are known [7,10].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…In contrast to Rural Postman, whose unweighted variant is NP-hard [12], we can show that EE and MEE are polynomial-time solvable. Altogether, our work complements and extends known results for WMEE with restricted weight function [11] and Rural Postman, for which mainly approximation, heuristic, and some polynomial-time algorithms for special cases are known [7,10].…”
Section: Introductionsupporting
confidence: 74%
“…For instance, it would be interesting to determine the parameterized complexity with respect to the parameter "number of weakly connected components" in a Weighted Multigraph Eulerian Extension instance. In this context, Orloff [17] observed that "the determining factor in the complexity of the problem seems to be the number (c) of connected components in the required edge set"; Frederickson [10] noted "the existence of an exact recursive algorithm that is exponential only in the number of disconnected components." However, it is doubtful that this meant fixed-parameter tractability with respect to c. In further future work, we also want to study the undirected and non-multigraph versions of WMEE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key issue in both problems is to determine the influence of the number c of connected components on each problem's computational complexity [10,17,18,23,29]. More precisely, c refers to the number of weakly connected components in the input graph for EE and the number of weakly connected components in the graph induced by the required arcs for RP.…”
Section: Introductionmentioning
confidence: 99%
“…If c = 1, then RP is efficiently solvable in polynomial-time [10]. Indeed, Frederickson [17,18] observed that, generally, RP is polynomial-time solvable when c is constant. However, c influences the degree of the polynomial in the running time of Frederickson's algorithm.…”
Section: Introductionmentioning
confidence: 99%